(untitled) - Anderson, David (Business Expert Press, 2012)
Ebook from IG Library ; Eighty percent of small to medium sized new businesses fail within 2 years of their inception. Ninety percent of businesses close after 10 years of operation. While many factors contribute to failure, the lack of an organized, measurable, strategic marketing plan often is the underlying cause. Creating a strategic marketing plan for your business may appear to be a daunting task. Indeed, many business owners do not create a strategic marketing plan or the plan they create is flawed due to the lack of an actionable planning process. 'Strategic Marketing Planning for the Small to Medium Sized Business' addresses these issues by providing both narrative marketing theory as well as workbook exercises. This book offers the small to medium sized business owner or marketing staff a hands-on experience that will culminate in the development of a true marketing plan, specifically tailored to an individual business. From developing or refining the company's mission, goals and strategies to implementing tactics and creating budgets, this book provides the information and framework needed to develop a sound marketing plan that will help your business grow.
Keywords: Marketing Strategy; Chiến lược tiếp thị; Quản lý tiếp thị